Chemical vapor deposition of graphene and its characterizations and applications - Nam, Jungtae; Yang, Jing; Zhao, Yue; Kim, Keun Soo (Current applied physics, 2024)
Chemical vapor deposition (CVD) plays a crucial role in reactions at the atomic and molecular levels, facilitating the growth of thin material layers and synthesizing various nano-electronic materials. This review focuses primarily on graphene as a representative example. The control of graphene properties is a significant and appealing aspect of graphene research. Graphene can be derived from natural graphite or artificially synthesized, with the latter offering relatively easier access and more straightforward property manipulation. This review delves into the intricate effects of doping and grain boundaries on CVD graphene properties, emphasizing modifications in atomic and electronic structures induced by nitrogen and boron dopants. In the case of single crystal CVD graphene, we have reviewed the transport properties of graphene devices, highlighting their extraordinarily high electronic quality comparable to exfoliated counterparts. In addition, in the final section, we briefly explore some representative application cases leveraging the unique advantages of large-area graphene. [Display omitted] •This review understands the concept of CVD from Nature and summarizes previous research papers on CVD grown graphene.•It evaluates the basic properties of graphene synthesized by the CVD and reviews methods for controlling these properties.•The emphasis is on the synthesis of both pure and doped graphene, with a description of potential applications.•Various application examples utilizing the advantages of large-area graphene are summarized.